Shallow Inferior Conjunctival Fornix in Contracted Socket and Anophthalmic Socket Syndrome: A Novel Technique to Deepen the Fornix Using Fascia Lata Strips - Mohamed F. K. Ibrahiem; Sahar T. A. Abdelaziz (Journal of Ophthalmology)
Purpose. To evaluate a new surgical technique using fascia lata to deepen the shallow inferior conjunctival fornix in contracted socket and anophthalmic socket syndrome. Methods. A prospective controlled study in which 24 sockets of 24 patients who were unable to wear and retain their ocular prosthesis due to shallow inferior fornix were enrolled and categorized into anophthalmic socket syndromes (9 patients) and contracted sockets (15 patients). Another 24 patients who underwent evisceration or enucleation with healthy sockets and can wear and retain their prosthesis comfortably were chosen as a control group. Deepening of the fornix was performed using fascia lata strips under general anesthesia. Central depth of the inferior fornix was measured preoperatively and postoperatively. Results. A statistically significant improvement of the postoperative central inferior fornix depth was reported which was marked in anophthalmic subgroup. 100% of anophthalmic sockets and 93.3% of contracted sockets achieved satisfactory results during the follow-up period with no postoperative lower eyelid malposition or obvious skin scar. Conclusion. Fascia lata technique is a new alternative and effective procedure to deepen the shallow inferior fornix that can be used in moderate to severe contracted sockets or anophthalmic socket syndrome with minimal lower eyelid or socket complications.